Relationship Between Water Quality andthePhytoplankton Abundanceof the Tanjung Balam Lake waters, Kampar District, Riau Province - Mustika Firdaus; Madju Siagian; Tengku Dahril (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTTanjung Balam Lake receive organic and anorganic matter from palm plantation and the water from the Kampar River. To understand the relationship between water quality and the phytoplankton abundanceof the Tanjung Balam Lake, a research has been conducted in June – July 2019. There were three sampling points, namely in the inlet, in the middle of the lake and in the end of lake. In each sampling point, the water was sampled from the surface and 2 Secchi depth. Samplings were conducted 3 times, once/week. Water quality parameters measured were temperature, transparency, depth, pH,dissolved oxygen, CO2, nitrate, phosphate and the abundance of phytoplankton. Results shown that the temperature was 28-30.30C, transparency was 49-52 cm, depth was 137.7-236.7 cm, pH was 5, dissolved oxygen was 4.03-6.57 mg/L, CO2 was 3.83-6.13 mg/L, nitrate was 0.016-0.030 mg/L and phosphate was 0.083-0.096 mg/L. There were 62 species of phytoplankton, namely Chlorophyceae (24 species), Trebouxiophyceae (5 species), Zygnematophyceae (4 species), Euglenophyceae (14 species), Bacillariophyceae (10 species), Chyanophyceae (4 species) and Cryptophyceae (1 species). The phytoplankton abundance in the lake was 431,394-891,640 cells/L. Data analysis indicate that any changing in water quality parameter will affect the abundance of phytoplankton. Keywords:Kampar River, Chlorophyceae, Cryptophyceae,Nitrate Concentration, Oxbow Lake